Piezoelectric inchworm actuator using silicon as the mechanical material. (22nd April 2021) - Hughes, George; Adams, Mark
Abstract: Piezoelectric inchworm actuators allow for a large stroke and high precision. This paper aims to minimize the footprint of the actuator by using semiconductor and MEMS fabrication techniques to build the frame and channel out of silicon wafers. The high precision of the semiconductor processes allows for precise tolerances as well as the ability to use batch processing for a shorter fabrication time. Using silicon as the mechanical material can also allow for the incorporation of the electrical signals into the frame.